Peer Educational Support for the Elderly of Malaria Prevention in Endemic Areas - Jumu, La; Sukatemin, Sukatemin; Hardy, Syaifoel (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
This study used a quantitative method with a purposive sampling design. The research was conducted in Mamoribo village, West Biak district, Papua. The objective was to provide evidence of the social support of education for the elderly by their peers in preventing malaria in endemic areas. The research population was 70 respondents. Primary data was obtained through a questionnaire. The inclusion criteria were elderly over 60 years old, residents of Mamoribo-Biak, family members or friends, and willingness to provide social support education. The exclusion criteria were not being elderly, people outside Mamoribo, or being elderly but not willing to provide social educational support. Secondary data were official documents from the Ministry of Health, WHO, and reputable journals in Indonesian and English languages published over the last five years. The data analysis used was univariate. The results showed that majority of the respondents were active farmers (45%) followed by housewives (25%). Willing to participate the program was 45%. While respondents who had been exposed to malaria n=58 (82.9%).  The attendance rate was on average 92.9% and shows a good indicator ( 70%). The major challenge was physical condition (31%). The conclusion was that the level of social support for peer education programs to prevent malaria in the elderly had the potential to participate in malaria eradication programs.